PENEGAKAN HUKUM KEIMIGRASIAN BERDASARKAN UNDANG-UNDANG NOMOR 6 TAHUN 2011 TENTANG KEIMIGRASIAN (PUTUSAN NOMOR 135/PID.SUS/2021/PT.BTN) - Sapta Adi Putra; Tri Sulityowati (Fakultas Hukum Universitas Trisakti, 2021)
Abdulbasset Al Qeblawi on the use of fake passports by foreign nationals. The use of fake passports is known at TPI Class I Terminal 3 Arrival of Soekarno-Hatta International Airport. The problem formulation is how the occurrence of immigration crimes in the form of using fake passport documents, how law enforcement is applied in cases of using fake passport documents, and how prevention efforts are made by Immigration to tackle foreigners who use fake passports. Normative juridical research method, using secondary data consisting of primary legal materials and secondary legal materials using qualitative analysis and deductive inference, the results of research, discussion and conclusions Abdulbasset Al Qeblawi is known to use a fake passport assisted by a Syrian agent named Mundzir, In law enforcement, special legal terms are used to override the general law because it is an immigration crime and is subject to Article 119 paragraph (2) of the Immigration Law, in preventing the use of fake passports, the Directorate General of Immigration makes efforts by tightening Indonesian immigration permits abroad and supervision of foreigners in Indonesia.